2014
DOI: 10.3382/ps.2013-03651
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of water-holding capacity in raw and freeze-dried broiler breast meat with visible and near-infrared spectroscopy

Abstract: The feasibility of using visible/near-infrared spectroscopy (vis/NIR) to segregate broiler breast fillets by water-holding capacity (WHC) was determined. Broiler breast fillets (n = 72) were selected from a commercial deboning line based on visual color assessment. Meat color (L*a*b*), pH (2 and 24 h), drip loss, and salt-induced water uptake were measured. Reflectance measurements were recorded from 400 to 2,500 nm in both raw and freeze-dried breast meat samples. Raw and freeze-dried samples had similar spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 30 publications
2
28
0
Order By: Relevance
“…Only minor differences were observed in the moisture contents of the high-CL and low-CL muscles. As also indicated in previous study [8], the WHC is closely connected with the membrane and structural integrity of cells in the muscle tissue. Table 2 shows the performances of models developed using PLS-DA and RBF-SVM with optimal preprocessing methods, respectively.…”
Section: Spectral Featuressupporting
confidence: 81%
See 3 more Smart Citations
“…Only minor differences were observed in the moisture contents of the high-CL and low-CL muscles. As also indicated in previous study [8], the WHC is closely connected with the membrane and structural integrity of cells in the muscle tissue. Table 2 shows the performances of models developed using PLS-DA and RBF-SVM with optimal preprocessing methods, respectively.…”
Section: Spectral Featuressupporting
confidence: 81%
“…Low-CL fillets exhibited higher reflectance signals at 550 nm and 492 nm than high-CL fillets, which indicated that the samples could be initially screened by meat color attributes (in accordance with the statistics in Table 1). Specifically, the bands at 980 nm and the weak valley at 762 nm were closely related to the presence of water in muscles, which could be attributed to the second and third overtone of O-H stretching mode of water, respectively [8,30]. Only minor differences were observed in the moisture contents of the high-CL and low-CL muscles.…”
Section: Spectral Featuresmentioning
confidence: 89%
See 2 more Smart Citations
“…Nowadays, chicken breast meat with quality assurance is becoming more expected and pursued by consumers. Water-holding capacity (WHC) is defined as the ability of muscle to retain water or resist water loss and is determined by a series of complicated physical structures and chemical components of chicken meat (i.e., diameter and density of muscle fibers and the integrity of connective tissue, as well as myofibrillar protein and collagen content) [2][3][4][5]. Meanwhile, a change in WHC is usually expressed as a change in texture in the meat to a large extent [6].…”
Section: Introductionmentioning
confidence: 99%